2000
DOI: 10.1093/humupd/6.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte-granulosa cell interactions

Abstract: In the past, different protocols of ovulation induction, aimed to overcome problems of anovulatory infertility in humans, have been developed during IVF programmes. However, administration of exogenous hormones may cause severe health problems, e.g. ovarian hyperstimulation syndrome. To overcome this problem an attractive alternative is to develop in-vitro systems that allow follicle and oocyte growth and maturation. This paper reviews the current status of research on oocyte-granulosa cell interactions and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(87 citation statements)
references
References 141 publications
2
73
0
12
Order By: Relevance
“…It has been shown that paracrine and low molecular weight factors establish an actual dialogue between oocyte and cumulus cells [8]. Oocyte quality is assured by LH-driven nutritional and informational signals emanating in cumulus cells [2,36] and, at the same time, oocyte-derived factors influence GC functions such as cumulus expansion, apoptosis, carbohydrate metabolism and steroidogenesis [53,54] influencing their own microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that paracrine and low molecular weight factors establish an actual dialogue between oocyte and cumulus cells [8]. Oocyte quality is assured by LH-driven nutritional and informational signals emanating in cumulus cells [2,36] and, at the same time, oocyte-derived factors influence GC functions such as cumulus expansion, apoptosis, carbohydrate metabolism and steroidogenesis [53,54] influencing their own microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…A complex crosstalk mediated by gap junctions and paracrine signaling occurs between the oocyte and surrounding cumulus cells (Canipari 2000). Bidirectional communications between both compartments of the COC enable each of them to coordinate their differentiation (Eppig 2001, Matzuk et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The maturation process in mammalian oocytes includes coordinate expression of autocrine and paracrine factors and, thereby, interactions among the cellular components of the follicles, somatic cells, and germ cells (2).…”
mentioning
confidence: 99%